2015
DOI: 10.3389/fmicb.2015.00553
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocytoplasmic transport of nucleocapsid proteins of enveloped RNA viruses

Abstract: Most viruses with non-segmented single stranded RNA genomes complete their life cycle in the cytoplasm of infected cells. However, despite undergoing replication in the cytoplasm, the structural proteins of some of these RNA viruses localize to the nucleus at specific times in the virus life cycle, primarily early in infection. Limited evidence suggests that this enhances successful viral replication by interfering with or inhibiting the host antiviral response. Nucleocapsid proteins of RNA viruses have a well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
61
0
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(67 citation statements)
references
References 85 publications
(116 reference statements)
0
61
0
6
Order By: Relevance
“…The causative agent of the current COVID-19 pandemic, SARS-CoV-2, is a single stranded positive sense RNA virus that is closely related to severe acute respiratory syndrome coronavirus (SARS-CoV). Studies on SARS-CoV proteins have revealed a potential role for IMPα/β1 during infection in signal-dependent nucleocytoplasmic shutting of the SARS-CoV Nucleocapsid protein (Rowland et al, 2005;Timani et al, 2005;Wulan et al, 2015), that may impact host cell division (Hiscox et al, 2001;Wurm et al, 2001). In addition, the SARS-CoV accessory protein ORF6 has been shown to antagonize the antiviral activity of the STAT1 transcription factor by sequestering IMPα/β1 on the rough ER/Golgi membrane (Frieman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The causative agent of the current COVID-19 pandemic, SARS-CoV-2, is a single stranded positive sense RNA virus that is closely related to severe acute respiratory syndrome coronavirus (SARS-CoV). Studies on SARS-CoV proteins have revealed a potential role for IMPα/β1 during infection in signal-dependent nucleocytoplasmic shutting of the SARS-CoV Nucleocapsid protein (Rowland et al, 2005;Timani et al, 2005;Wulan et al, 2015), that may impact host cell division (Hiscox et al, 2001;Wurm et al, 2001). In addition, the SARS-CoV accessory protein ORF6 has been shown to antagonize the antiviral activity of the STAT1 transcription factor by sequestering IMPα/β1 on the rough ER/Golgi membrane (Frieman et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…The NS1 protein of influenza virus prevents caspase-1 activation and the secretion of IL-1b and IL-18 via an unknown mechanism. The IL-1b and IL-18 pathways have been observed to be regulated by the vaccinia virus protein B15R and the molluscum contagiosum poxvirus proteins MC53L and MC54L, which can bind and inhibit IL-1b and IL-18, respectively [132,133]. Thus, the viral alkaline exonuclease of Epstein Barr virus (BGLF5) down-regulates molecules of the immune system such as TLR-2 and CD1 by degrading the mRNAs that encode them [134].…”
Section: Regulation Of the Inflammasomementioning
confidence: 99%
“…Viral RNPs are transported to the cell nucleus where the virion polymerase complex synthesizes mRNA species(262). Another tentative function of the NP could be associated to the potential interference of the host immune response in the nucleus mediated by capsid proteins of some RNA virus, which could inhibit host transcription and thus liberate and direct it to viral RNA synthesis(263). mRNA synthesis is primed by capped RNA fragments 10-13 nt in length that are generated by cap snatching from host nuclear RNAs which are sequestered after cap recognition by PB2 and incorporated to vRNA by PB1 and PA proteins which present viral endonuclease activity(264).…”
mentioning
confidence: 99%